Leveraging Neuroscience to Fight Stigma Around Mental Health - Almeida, Osborne F. X.; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2022)
Labels serve as identifiers and convenient descriptors of inanimate and animate objects. In humans, given labels can easily become part of an individual’s self-perceived identity. Negative labels ascribed to a person can result in internalized stigma, a state that will shape the subject’s biography. This can ultimately impact on the person’s mental and physical health since perceived and/or anticipated stigma discourage social- and health-seeking services (Wahl 2012). Per definition, stigma involves labelling of persons with physical, mental, or social characteristics that do not match the observer’s arbitrarily conditioned and calibrated sense of norms (public stigma) that may eventually become embedded in rules, regulations, and laws (structural stigma). Internalized stigma projects onto a person’s emotions and actions. Public (enacted) stigma results from stereotyping (collectively agreed-upon notions about a group of persons that are used to categorize these people) and devaluation, which subsequently leads to social distancing, discrimination, and blatant abuse of human rights (Maj, 2011). Much of what we know about stigma results from research in the psychosocial sciences and, more recently, from social neuroscience. Stigma around mental health has generated much attention in the field of psychiatry where, to date, most research has focussed on epidemiology and anti-stigma interventions. This essay intends to stimulate debate, thought, and research within the community of behavioral neuroscientists and, therefore, to inform evidence-based design and implementation of neuroscience-based approaches by other professionals working towards the elimination of the stigma attached to mental illness.